PEMETAAN GERAKANTANAH DAN ANALISIS KESTABILAN LERENG DESA GONDANGLEGI, KECAMATAN KLEGO, KABUPATEN BOYOLALI, JAWA TENGAH - Fakhlove Wardhani; Dwiyanto Joko Suprapto; Wahju Krisna Hidajat; Citra Ningtyas (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Massmovement disaster is very harmful, because it can damage various infrastructure facilities. Gondanglegi villages, subdistricts Klego, Boyolali district, Central Java, an area that suffered massmovement was quite severe in recent years.To find out how prevention of landslides in the study location so that need to do geotechnical investigations surface and subsurface. Surface investigations conducted by geotechnical mapping aimed to find out surface conditions that include geotechnical conditions and the direction of ground motion distribution / landslides. While subsurface investigation conducted by using data from the PT . Selimut Bumi Adhi Cipta form of with core drilling to a depth of 15 meters data which then laboratory testing, and also geoelectric investigation data.From the data results of the investigation like slope geometry, subsurface cross-section, the interpretation of landslide areas and mechanical properties of soil/ rock material slope stability analysis that using softwares like Slide version 8.0 and Phase ver 8.0.Based on the results of the slope stability analysis, slope conditions around the cross-section AA' and BB' classified as unsafe have a safety factor value ( Fs ) of 0.851 to 1.031. And the area around the cross-section CC' is safe, with a factor of safety value ( FS ) at 4.33Type of massmovement that occurs at the study location in the form is rotational slides with a speed that is classified as moderate massmovement caused by high levels of steepness of slopes and thick weathering materials and triggered by rainfall and human activities.Alternative of prevention to do is cut off the top of the slope, cut down slope, installing gabion stone, make some retaining walls and grouting.